Systemic and Oral Immunogenicity of Porcine Epidemic Diarrhea Virus Antigen Fused to Poly-Fc of Immunoglobulin G and Expressed in ΔXT/FT Nicotiana benthamiana Plants - Nguyen-; Nguyen-; Moon-Sik Yang; Moon-Sik Yang; Yong-Suk Jang; Tae-Ho Kwon; Rajko Reljic; Mi-young Kim; Mi-young Kim (Frontiers Media S.A., 2021)
Porcine epidemic diarrhea virus (PEDV), a member of the Coronaviridae family has become increasingly probelmatic in the pig farming industry. Currently, there are no effective, globally applicable vaccines against PEDV. Here, we tested a recombinant PEDV vaccine candidate based on the expression of the core neutralising epitope (COE) of PEDV conjugated to polymeric immunoglobulin G scaffold (PIGS) in glycoengineered Nicotiana benthamiana plants. The biological activity of COE-PIGS was demonstrated by binding to C1q component of the complement system, as well as the surface of antigen-presenting cells (APCs) in vitro. The recombinant COE-PIGS induced humoral and cellular immune responses specific for PEDV after both systemic and mucosal vaccination. Altogether, the data indicated that PEDV antigen fusion to poly-Fc could be a promising vaccine platform against respiratory PEDV infection.